Electromagnetic fields in nonuniform disk-loaded waveguides - Ayzatsky, M.I.; Mytrochenko, V.V. (Вопросы атомной науки и техники, 2016)
On the base of general approach we obtain some results that can be useful in the process of tuning of nonunifrom disc-loaded waveguides. Our consideration has shown that simple values that characterize the detuning of the cells can be introduced only for the disc-loaded waveguide with parameters that change very slow. In general case it is needed to conduct full numerical simulation of specific disc-loaded waveguide and obtain all necessary coupling coefficients. After that one can start the tuning process on the base of bead-pull field distribution measurements.